Review of the species of Betasyrphus Matsumura, 1917 (Diptera: Syrphidae) from Madagascar with description of a new species - Ssymank, Axel (Zootaxa, 2010)
The species of the genus Betasyrphus Matsumura, 1917 from Madagascar are reviewed. Betasyrphus keiseri sp. nov. is described from Vohipara (Ramonafana National Park) and compared to the type material of Betasyrphus serarius (Wiedemann,1830). The latter species could not be confirmed from the Afrotropical region and has to be deleted from the Afrotropical catalogue. The male genitalia of the new species are figured and a key to the species from Madagascar is given. The genus contains 12 described Aftrotropical species, excluding two taxa of uncertain status. Only two valid species exist in Madagascar.